(3MGTjI GdbGRGHGOi Ydi GdHjVGhis - (3CHh GdfGaY CMeO Hf eMeO Hf ESMb GdQhei , GdbGRCHGOis; (3YHO Gddg Hf YeQ Hf eMeO Hf Ydj GdTjQGRj, CHh SYjO CHh GdNjQ fGUQ GdOjf GdHjVGhj,J (B685 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Gdedc GdMb GdeHjf hHYO ajbhd GdeaJbQ Edi QHg GdebJOQ CHh GdfGaY CMeO HfeMeO GdbGRCHGOi gPg fHPI ef GdcdeGJ hTF jSjQ ef GdfcGJ cJHJgG Ydi HYV JaSjQ GdYdGeI GdbGVi s
(3BNQgG (B:s
(3LhGH Yf SDGd Yf SHH LeY GdbJQI eY GdZjQI agh ESJFfGa hajg OdGdI Ydi Cf GdcaGQ ecdahf HGdaQhY ai Mb GdeDGNPI ai GdBNQI hdG NdGa ajg JeJ GdMhGTi s
(3cJH Ydi GdZdGa YdGejI bGRCHGOi Ydi GdHjVGhi ef ShQI GdfHC Edi ShQI YHSs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B110 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B298s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B333s
Keywords: (3GdJaSjQ hYdhe GdbQBfs